Tinjauan Peran Dan Sifat Material Yang Digunakan Sebagai Scaffold Dalam Rekayasa Jaringan - Ellyza Herda; Dewi Puspitasari (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2018)
Tissue engineering aims to restore, maintain, or improve tissue functions that are defective or have been lost by pathological, phisiological and mechanical or traumatic conditions by developing biological substitutes or by reconstructing tissues. Stem cells, scaffolds and growth factor are the key components of engineered tissues and referred as the tissue engineering triad. Scaffold has an important role in providing a microenvironment to assist stem cells to make adhesion, proliferation and differentiation in order to produce the expected tissue. The scaffold should be designed in order to have the expected properties. This paper aims to discuss the function of the scaffold, properties must be owned by the scaffold and the type of material. Size, shape and the type of material, pore size and interconnetivity, influencing the behavior and function of stem cell therefore influence stem cells fate.